RITUAL DAN NILAI ISLAMI DALAM FOLKLOR JAWA - Bani Sudardi (IBDA` : Jurnal Kajian Islam dan Budaya, 2015)
This research is about ritual and Islamic value in Javanese folklore. The research shows that Islamic values are found in many Javanese ritual and mixed with the former ritual. The former ritual is added with Islamic values e.g. reciting Holly Quran, pray, or appeared with Islamic characters such as Nabi Sulaiman, Nabi Khidir and Syaikh Karim. The method is qualitative research method along with observation, in-depth interview, and content analysis. The Islamic rituals have growth rapidly since Islam became the ideology of Mataram Kingdom/ Kasunanan. Islam is legitimated by the story of Brawijaya (latest Majapahit’s king) who believe and convert to Islam and change his name to be Sunan Lawu. The forms of Islamic ritual are sadranan (ritual in cemetery), reciting Yaasin together, praying, marriage ritual, and grebeg in Kasunanan Palace.